A FEW THEMES ABOUT EDUCATION IN THE LIBERAL SALVADORIAN PRESS (1870-1890); WOMEN AND WORKERS WITH A LAIC EDUCATIONAL BACKGROUND - Herrera Mena, Sajid Alfredo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
This article briefly explorer three issues posed by some salvadorean liberals by the end of nineteenth century. The civil emancipation of women through a new approach to education, the creation of night school for artisans or institutes to teach agriculture to peasants and election of secular education became key issues for political, social and economic development in the country. These analyses were collected from local newspapers published between 1870 and 1890: Diario Oficial, La Discusión, La República, La Unión and el Boletín municipal de Santa Ana.